From noise to protein with image models - Amini, Ava P.; Yang, Kevin Kaichuang (Nature Computational Science, 2023)
An image-inspired deep-learning model is developed to generate realistic de novo protein structures and scaffolds around functional sites, which helps the search for new structures and functions in protein engineering.